x(x-3)(x+12)=324

Simple and best practice solution for x(x-3)(x+12)=324 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(x-3)(x+12)=324 equation:


Simplifying
x(x + -3)(x + 12) = 324

Reorder the terms:
x(-3 + x)(x + 12) = 324

Reorder the terms:
x(-3 + x)(12 + x) = 324

Multiply (-3 + x) * (12 + x)
x(-3(12 + x) + x(12 + x)) = 324
x((12 * -3 + x * -3) + x(12 + x)) = 324
x((-36 + -3x) + x(12 + x)) = 324
x(-36 + -3x + (12 * x + x * x)) = 324
x(-36 + -3x + (12x + x2)) = 324

Combine like terms: -3x + 12x = 9x
x(-36 + 9x + x2) = 324
(-36 * x + 9x * x + x2 * x) = 324
(-36x + 9x2 + x3) = 324

Solving
-36x + 9x2 + x3 = 324

Solving for variable 'x'.

Reorder the terms:
-324 + -36x + 9x2 + x3 = 324 + -324

Combine like terms: 324 + -324 = 0
-324 + -36x + 9x2 + x3 = 0

The solution to this equation could not be determined.

See similar equations:

| 3x+6y=-9 | | 7x+4y=53500 | | 2m-4=10+16 | | F(t)=0.25t^2-0.5t+3.5 | | 26=-7x+5(x+8) | | c+4=3/4 | | 6x-(5x+4)=5x-32 | | -3t-8+7t=35+9t-2 | | 40.5=49+1.7(55-60) | | 6=7x+69 | | 14y=32 | | 10lnx=e^4 | | 6st-7su+5sv= | | y=11x^2+x+40 | | 3y=-2x+11 | | 2+7x=4x+8 | | ln(10lnx)=4 | | 6a=-18 | | 18p^2-18=77p | | -9+-6y+6y=-9 | | (5x-12)+(3x-2)=180 | | 4p-3q=23 | | j+556=-7 | | 0.21x+252.00=850 | | 6+40=15x-50 | | 4x+70= | | ln(x-1)-ln(x+1)=2 | | 10x+15y=6 | | 0x+15y=6 | | 8d-(2+d)=42 | | 3p+2q=17 | | 8-7+3= |

Equations solver categories